Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jcot.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

An unreported case of Streptococcus cristatus septic arthritis of wrist in a neonate

Abstract: Septic Arthritis of the wrist is rare in the paediatric population due to its extraarticular metaphysis. We report here a case of wrist septic arthritis in a neonate caused by an uncommon causative organism, Streptococcus cristatus.A 15 days old male child was referred with the complaint of swelling and decreased movement of the left wrist for 5 days. Local examination revealed warm, tender, erythematous and fluctuant swelling over the dorso-ulnar aspect of the left wrist. Ultrasonography of the affected regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…Between the 5 case reports that we found8–11,13 and the 3 patients in our series, we are aware of only 8 cases of pediatric septic arthritis of the wrist described in the literature. Wrist septic arthritis in children may be more likely to be caused by an atypical organism, including Streptobacillus moniliformis from a rat bite,9 group A Streptococcus pyogenes,13 and Streptococcus cristatus 10. In our series, we had 1 case each of wrist septic arthritis caused by Streptococcus and Gram negative rods.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Between the 5 case reports that we found8–11,13 and the 3 patients in our series, we are aware of only 8 cases of pediatric septic arthritis of the wrist described in the literature. Wrist septic arthritis in children may be more likely to be caused by an atypical organism, including Streptobacillus moniliformis from a rat bite,9 group A Streptococcus pyogenes,13 and Streptococcus cristatus 10. In our series, we had 1 case each of wrist septic arthritis caused by Streptococcus and Gram negative rods.…”
Section: Discussionmentioning
confidence: 80%
“…Wrist septic arthritis in children may be more likely to be caused by an atypical organism, including Streptobacillus moniliformis from a rat bite, 9 group A Streptococcus pyogenes, 13 and Streptococcus cristatus. 10 In our series, we had 1 case each of wrist septic arthritis caused by Streptococcus and Gram negative rods.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, phylogenetic studies performed by Teng JL et al in 2014 have shown that S. oligofermentans is closely related to Streptococcus sinensis and a new phylogenetic clade, the "sinensis group", has been proposed to include Streptococcus sinensis, S. oligofermentans and S. cristatus [4]. Currently, only eight clinical cases of infections caused by this microorganism have been described: one case of bacteremia, six cases of infectious endocarditis, and another of septic arthritis (Table 1) [5][6][7][8][9]. This is the sixth confirmed case of endocarditis after the microorganism by sequencing the 16S ribosomal RNA gene when processing the surgical specimen of a replaced heart valve.…”
mentioning
confidence: 99%